Unemployment and economic growth in Cote D'ivoire: A disaggregated approach to growth using the Shapley decomposition - Gaudens-Omer, Kouakou Thiedje (Growth, 2025)
This study analyzes the responsiveness of unemployment to the variation in production in Côte d'Ivoire over the period 1980-2019. By using three approaches of Okun's law (model in difference, model in gap, and disaggregated growth model), we estimate long-term and short-term relationships via error correction models (ECM). The first two approaches highlight the weak link between economic growth and unemployment. The third approach, based on the Shapley decomposition, shows that this low responsiveness of unemployment to the variation in production is essentially due to the fact that final consumption and public expenditure, which largely explain the variability of unemployment, have a very low impact on the unemployment rate. This results from the extroverted nature of the Ivorian model of economic growth. The study recommends that public authorities relocate the production of most consumer goods and equipment, step up policies to promote local industries aimed at replacing certain imported consumer goods and equipment, and strengthen the public procurement and contracts policy in favor of local businesses.